Income comparison, collectivism and life satisfaction in Turkey - DUMLUDAĞ, DEVRİM; GİRAY YAKUT, SELAY (SPRINGER, 2016)
The current research examines the impact of income comparisons on life satisfaction in Turkey which has a feature of collectivism or low individualism. This is done by analyzing the results of the Life Satisfaction Survey applied by the Turkish Statistical Institute (TUIK) for 2011. Using ordered logit estimations, this paper reveals that most of the income comparison, interaction variables and socio-economic variables have a significant explanatory power on life satisfaction levels in Turkey. The main emphasis of the paper is that reference group's self-reported life satisfaction is related to income comparisons, along with other socioeconomic factors. The impact of comparisons is asymmetric, in that in most cases, under-performing one's benchmark had a greater effect than out-performing it.
Keywords: Relative income; Income comparison; Life satisfaction; Turkey; SELF-ESTEEM; HAPPINESS; TRANSITION; GROWTH